(untitled) (Global Journal of Medical Research, 2019)
Following the Economic Partnership Agreement (EPA) between Japan and Indonesia coming into effect, acceptance of Indonesian nursing and care worker candidates began in 2008. From the following fiscal year, acceptance was expanded to include the Philippines and Vietnam. The medical and nursing care fields in Japan are gradually becoming internationalized. We speculated that EPA candidates would adapt to living and working in Japan, which has a different culture from their own country. This study assessed their adaptability to Japanese culture, mental health, and the clarified factors related to their mental health, based on the results of a quantitative survey.